Activity Effects on Path Integration Tasks for Children in Different Environments - Neidhardt, Eva; Popp, Michael (Spatial Cognition VIII, 2012)
In each of the three presented studies kindergarten children and school children walked a path of about one kilometer in a macro environment At up to six locations subjects stopped and were asked to point into the direction of the path origin with their outstretched arm and finger and later with a mechanical pointer or, in the case of the virtual environment, with a laser pointer. Pointing accuracy was taken as a measure for path integration. Kindergarten children from small German towns and from a primary school in Namibia as well as school children from Munich were tested. The Munich school children were also assessed in a virtual reality condition. Results indicate that children’s activity reports influence pointing accuracy. Implications for gender differences and ideas on affordances of children’s future real environments are discussed.